An Assessment of West Kalimantan’s Electricity System - HASANAH NUR (Graduate School of International Studies Ajou University, 2024)
Indonesia regarded as the world's fourth densely populated country and the region's largest economy. Due to the country's financial solid and statistical development, power demand in Indonesia has increased over the past ten years at a rate of 6% per year. Fossil fuels estimated to account for more than 90% of Indonesia's power generation capacity, have so far primarily met this demand. Nearby the growth in the use of fossil fuels, Indonesia's CO2 emissions have sharply increased. Therefore, the energy planning’s role in evaluating the future energy framework and advising policymakers is critical, especially in setting goals to decrease the emissions of greenhouse gas (GHG). Electricity process production is the primary source of global GHG emissions. It is critical to select resources that emit the fewest hazardous emissions during generation of electricity. These considerations recommend the Low Emissions Analysis Platform (LEAP) demonstration, which analyzes a regular daily situation and GHG correlational circumstances to enhance West Kalimantan's power generation from 2021 to 2030. The West Kalimantan Province has strong potential to fulfill energy demand itself, or nearby along with the capital city of Indonesia, will move to the East Kalimantan Province. According to 2021 Statistics Indonesia data, the population of West Kalimantan Province is around 5.47 million, with the population growth rate in 2010- 2021 being 1.39%/year, and the economic growth grew by 4.78%. The current study is based on a bottom-up examination of West Kalimantan, Indonesia's energy supply framework. This investigation aims to broaden the evidence base required to advise approach and procedure dialogues within the Indonesian government and related communities regarding selecting a GHG emission reduction target for 2030. On the energy supply side, the investigation provides detailed insights into approaching diminished energy and outflow force. The limitation of the study is only focused on the energy framework within the electricity sector. Information input for this study is from official report of PT PLN, Indonesia's government electricity company. _x000D_ Keywords : Energy system model, Local electricity supply-demand analysis, Climate change, LEAP
학위논문(석사)--융합에너지학과,2024. 2
Keywords: Energy system model; LEAP; Local electricity supply-demand analysis; climate change